Association of Dietary Patterns with Some Risk Biomarkers of Chronic Kidney Disease of Saudi Patients : Association of Dietary Patterns with CKD Biomarkers - Khogali, Fathia (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2020)
Chronic kidney disease (CKD) is a worldwide public health problem. There have been a marked rise in the prevalence of (CKD) in Saudi Arabia. This study aimed to identify dietary pattern of Saudi CKD patients and to evaluate the relationship between dietary patterns and the biomarkers in CKD. The study was conducted among 58 previously diagnosed with CKD, both genders, aged > 70 years. Information regarding dietary patterns, demographic and medical history variables was obtained with an online questionnaire. Four dietary patterns, were identified, explaining 54.06% of the variance; Veggie Dietary Pattern, Plant-based Dietary Pattern, Miscellanies Pattern, and Animal-based Dietary Pattern. Correlation between dietary patterns and the metabolic risk factors of CKD; glomerular filtration rate (G3a, G3b), Serum creatinine, and albumin/creatinine ratio, showed inverse significant association with Veggie Dietary Pattern and the metabolic risk factors (r -0.591 P .008, r -0.574 P.015, r -.607 P.007, r -.601P.007) respectively. while Animal-based Dietary Pattern was most closely associated with metabolic risk factors (r.557 P.021, r.551 P.023, r.661,P.001,r.660 P.001) respectively. Marginally significant association was found between Plant-based Dietary Pattern and Miscellanies Pattern with CKD complications. After adjustment for age, gender, and BMI same correlation still found.